2008
DOI: 10.1055/s-2008-1067890
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysma aortae abdominalis und Beinamputation: Zufällige Koinzidenz oder pathogenetische Korrelation?

Abstract: A retrospective analysis of 545 patients, operated on between 1970 and 1987 for a closed or ruptured infrarenal aneurysm of the abdominal aorta (AAA), revealed an incidence of 5.1% of unilateral leg amputations among them (20 above, 8 below the knee) during the Second World War. Patients in both groups (with or without amputation) had one or more arteriosclerotic risk factors, their frequency rising with increasing age. There were differences between the two groups in the frequency of certain morphological cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For example, Crawford et al [ 100 ] demonstrated that reductions in aortic outflow from iliac occlusive disease are associated with increased peak wall stress and rupture of AAAs at smaller sizes. These studies are supported by historical data that demonstrated higher AAA rupture rate in patients with surgical ligation of the iliac arteries, which was done in combination axillo-bifemoral bypass as an experimental treatment for AAA, as well as in patients with reduced aortic outflow due to previous lower extremity amputations [ 101 , 102 ]. Moreover, Haller et al [ 103 ] found that increased ILT burden is associate with an increased risk of rupture in small AAAs (<6 cm).…”
Section: Studies and Limitationsmentioning
confidence: 75%
“…For example, Crawford et al [ 100 ] demonstrated that reductions in aortic outflow from iliac occlusive disease are associated with increased peak wall stress and rupture of AAAs at smaller sizes. These studies are supported by historical data that demonstrated higher AAA rupture rate in patients with surgical ligation of the iliac arteries, which was done in combination axillo-bifemoral bypass as an experimental treatment for AAA, as well as in patients with reduced aortic outflow due to previous lower extremity amputations [ 101 , 102 ]. Moreover, Haller et al [ 103 ] found that increased ILT burden is associate with an increased risk of rupture in small AAAs (<6 cm).…”
Section: Studies and Limitationsmentioning
confidence: 75%
“…Increased peripheral vascular resistance resulting in an increased risk of rupture of AAA was reported. 3 Moreover, Crawford and colleagues reported that mean and maximum wall stress was more than doubled with AOO compared with patent aortic outflow. 4 However, the initial symptoms were abdominal pain and back pain, and we could not find any white thrombus.…”
Section: Discussionmentioning
confidence: 99%